Associations between sleep apnea and advanced brain aging in a large-scale population study - Weihs, Antoine; Frenzel, Stefan; Wittfeld, Katharina; Obst, Anne; Stubbe, Beate; Habes, Mohamad; Szentkirályi, András; Berger, Klaus; Fietze, Ingo; Penzel, Thomas; Hosten, Norbert; Ewert, Ralf; et al. (Sleep (New York, N.Y.), 2021)
Abstract Advanced brain aging is commonly regarded as a risk factor for neurodegenerative diseases, for example, Alzheimer’s dementia, and it was suggested that sleep disorders such as obstructive sleep apnea (OSA) are significantly contributing factors to these neurodegenerative processes. To determine the association between OSA and advanced brain aging, we investigated the specific effect of two indices quantifying OSA, namely the apnea–hypopnea index (AHI) and the oxygen desaturation index (ODI), on brain age, a score quantifying age-related brain patterns in 169 brain regions, using magnetic resonance imaging and overnight polysomnography data from 690 participants (48.8% women, mean age 52.5 ± 13.4 years) of the Study of Health in Pomerania. We additionally investigated the mediating effect of subclinical inflammation parameters on these associations via a causal mediation analysis. AHI and ODI were both positively associated with brain age (AHI std. effect [95% CI]: 0.07 [0.03; 0.12], p-value: 0.002; ODI std. effect [95% CI]: 0.09 [0.04; 0.13], p-value: < 0.0003). The effects remained stable in the presence of various confounders such as diabetes and were partially mediated by the white blood cell count, indicating a subclinical inflammation process. Our results reveal an association between OSA and brain age, indicating subtle but widespread age-related changes in regional brain structures, in one of the largest general population studies to date, warranting further examination of OSA in the prevention of neurodegenerative diseases.